Effect of Altitude on Nutrient Concentration, Nutrient Stock and Uptake in Fine Root of Sal (Shorea Robusta Gaertn.) Forest in Terai and Hill Areas of Eastern Nepal - Bhattarai, Krishna Prasad; Mandal, Tej Narayan; Gautam, Tilak Prasad (Journal of Institute of Science and Technology, 2020)
The present study was conducted to understand the effect of altitude on the nutrient concentration, nutrient stock, and uptake in the fine root of the Terai Sal forest (TSF) and Hill Sal forest (HSF) in eastern Nepal. Annual mean fine root biomass in 0-30 cm soil depth was found higher in HSF (6.27 Mg ha-1) than TSF (5.05 Mg ha-1). Conversely, fine root production was higher in TSF (4.8 Mg ha-1 y-1) than HSF (4.12 Mg ha-1 y-1). Nitrogen, phosphorus, and potassium content in fine roots were slightly higher in TSF than HSF. Nutrient concentration in fine roots of smaller size (<2 mm diameter) was nearly 1.2 times greater than that of larger size (2–5 mm diameter) in both forests. In HSF total stock of different nutrients (kg ha-1) in fine root was 55.62 N, 4.99 P, and 20.15 K whereas, these values were 49.49 N, 4.14 P, and 19.27 K only in TSF. However, total nutrient uptake (kg ha-1y-1) by fine root (both size classes) was greater in TSF (48.5 N, 4.3 P, and 18.6 K) than HSF (36.9 N, 3.3 P, and 13.5 K). The variability in fine root nutrient dynamics between these two forests was explained by the differences in fine root biomass and production which were influenced by the combined effect of varied altitude and season. The fine root, as being a greater source of organic matter, the information on its nutrient dynamics is inevitable for the management of soil nutrients in the forest ecosystem.